2009
DOI: 10.1007/s00423-009-0465-0
|View full text |Cite|
|
Sign up to set email alerts
|

Malignant fibrous histiocytoma—pleomorphic sarcoma, NOS gene expression, histology, and clinical course. A pilot study

Abstract: The classification of these tumors may undergo further changes in the future. Gene expression profiling can provide additional information to categorize pleomorphic sarcoma (NOS) and reveal potential prognostic factors in this "entity."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…There is a little data about KRR1 function in tumors. It was suggested only that KRR1 is associated with metastasis in malignant fibrous histiocytoma [23]. During this study, we identified for the first time increased frequency of antibody response toward KRR1 antigen in sera of breast cancer patients and in sera of patients with invasive ductal breast carcinoma compared with sera of healthy women.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…There is a little data about KRR1 function in tumors. It was suggested only that KRR1 is associated with metastasis in malignant fibrous histiocytoma [23]. During this study, we identified for the first time increased frequency of antibody response toward KRR1 antigen in sera of breast cancer patients and in sera of patients with invasive ductal breast carcinoma compared with sera of healthy women.…”
Section: Discussionmentioning
confidence: 62%
“…Today more than 2000 TAAs have been identified by different approaches including SEREX, SEPRA, phage display, microarray, and other high throughput technologies [14, 23]. Previously, we have described 81 autoantigens identified from breast, colon, and thyroid cancers by SEREX approach [10, 12, 13, 15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that at least in some MFH of the bladder, other prognostic parameters might be at play. Recently, gene expression profiling disclosed up-or downregulation of a great variety of different genes in MFH [25]. Hopefully, it remains to be seen whether these results might yield novel predictive parameters to be employed for prognostic ramification of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical ablation with clear resection margins remains the therapy of Wrst choice (Al-Benna and Steinstrasser 2009;Al-Benna et al 2010). Radiation therapy has proven to be an eVective adjunct in gaining local tumour control (Clarkson and Ferguson 2004;Daigeler et al 2009Daigeler et al , 2010Fletcher et al 2002a, b;Pisters 2002). Distant metastases commonly into the lungs and local tumour relapse still remain unsolved clinical problems in the treatment of soft tissue sarcomas (Vezeridis et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Sarcomas display a high rate of chemoresistance. Hence chemotherapy at present is reserved for advanced tumour state (Daigeler et al 2009(Daigeler et al , 2010Pisters 2002;Potter et al 1985). The up to 50% rate of tumour relapse remains high (Pisters 2002).…”
Section: Introductionmentioning
confidence: 99%